In vivo-in vitro tumour cell lines: characteristics and limitations as models for human cancer. - Rockwell, S. (Nature Publishing Group, 1980)
In vivo-in vitro tumour cell lines are widely used to study the biology of cancer and to examine the factors influencing the response of tumours to therapeutic agents and regimens. The existing in vivo-in vitro tumours form a uniform and artificial population of experimental neoplasms, with biological characteristics which limit the acceptability of any of these tumours or panel of these tumours as an accurate model for human cancer. All are rapidly growing, transplanted tumours in highly inbred rodents. All have growth rates, cell proliferation patterns and tumour-host interactions different from those of primary tumours in animals or man. Most are immunogenic. Most are anaplastic sarcomas: few are carcinomas; none are well differentiated. The biological differences between in vivo-in vitro tumours and human neoplasms must be considered when the experimental systems are used as models for human cancer.